Implementation of Community-Based Occupational Therapy for Stroke Patients in Functional Activities Using Assistive Device: Case Study - Hermito Gidion; Muhammad Luthfi; Dini Fajariani (Proceedings, 2023)
Stroke is the major cause of disability globally. This disease can affect the patient’s independence and functional mobility severely. Community-based occupational therapy is expected to improve the post-stroke patient’s movement and independence to perform daily activities. This study aims to evaluate the effectiveness of community-based occupational therapy, providing assistive technology to a post-stroke patient with left-side paralysis in Situsari village. The data were collected through the direct implementation of occupational therapy and semi-structured interviews with clients and families. Based on the evaluation, the results show a significant increase in the independence level and occupational performance after using assistive technology.